Developmental Trends and Research Hotspots in Bronchoscopy Anesthesia: A Bibliometric Study - Min, Keting; Wu, Yutong; Wang, Sheng; Yang, Hao; Deng, Huimin; Wei, Juan; Zhang, Xiaowei; Zhou, Huanping; Zhu, Wanli; Gu, Yang; Shi, Xuan; Lv, Xin (Frontiers in Medicine, 2022)
Background This study discusses the developmental trends and research hotspots in bronchoscopy anesthesia in the past six decades. Methods The original and review articles published from 1975 to June 2021 related to bronchoscopy anesthesia were retrieved from the Web of Science Core Collection (WoSCC). Three different scientometric tools (CiteSpace, VOSviewer, and Bibliometrix) were used for this comprehensive analysis. Results There was a substantial increase in the research on bronchoscopy anesthesia in recent years. A total of 1,270 publications were retrieved up to June 25, 2021. Original research articles were 1,152, and reviews were 118, including 182 randomized controlled trials (RCTs). These publications were cited a total of 25,504 times, with a mean of 20.08 citations per publication. The US had the largest number of publications (27.6%) and the highest H-index of 44. The sum of publications from China ranked second (11.5%), with an H-index of 17. Keyword co-occurrence and references co-citation visual analysis showed that the use of sedatives such as dexmedetomidine in the process of bronchoscopy diagnosis and treatment was gradually increasing, indicating that bronchoscopy anesthesia was further progressing toward safety and comfort. Conclusion Based on a bibliometric analysis of the publications over the past decades, a comprehensive analysis indicated that the research of bronchoscopy anesthesia is in a period of rapid development and demonstrated the improvement of medical instruments and surgical options that have significantly contributed to the field of bronchoscopy anesthesia. The data would provide future directions for clinicians and researchers in relation to bronchoscopy anesthesia.